2022
DOI: 10.1177/19458924221114255
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Clustering of Olfactory Phenotypes

Abstract: Background Current clinical classifications of olfactory function are based primarily upon a percentage of correct answers in olfactory identification testing. This simple classification provides little insight into etiologies of olfactory loss, associated comorbidities, or impact on the quality of life (QOL). Methods Community-based subjects underwent olfactory psychophysical testing using Sniffin Sticks to measure threshold (T), discrimination (D), and identification (I). The cognitive screening was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“… 36 , 37 , 38 However, R. J. Schlosser focused more on olfaction and the surgical treatment of CRS. 39 , 40 , 41 …”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 , 38 However, R. J. Schlosser focused more on olfaction and the surgical treatment of CRS. 39 , 40 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…plasminogen activator, and oral CRTH2 antagonist [36][37][38] . On the other hand, Prof. Schlosser Rodney J focused more on olfaction and the surgical treatment of CRS [39][40][41] .…”
Section: Leading Experts and Related Directionsmentioning
confidence: 99%
“…2 On a broader level, olfactory testing and cognitive testing utilized for unsupervised clustering was shown by Schlosser et al to provide clinical phenotypes to identify patients with unique risk factors for heart disease, cancer, and diabetes. 3 Similarly, increased awareness of social determinants of health and high-risk exposures for chronic rhinosinusitis are valuable tools for clinicians to be aware of to help with comprehensive treatment and risk assessment for patients. Salman et al demonstrated that age, race, and employment status were significant predictors of high-acuity emergency room visits for patients with sinusitis, and Gill et al found that tobacco exposure increased the adjusted risk of revision sinus surgery, particularly in those with concurrent asthma diagnosis.…”
mentioning
confidence: 99%
“…2 On a broader level, olfactory testing and cognitive testing utilized for unsupervised clustering was shown by Schlosser et al to provide clinical phenotypes to identify patients with unique risk factors for heart disease, cancer, and diabetes. 3…”
mentioning
confidence: 99%